(untitled) (Global Journal of Management and Business Research, 2024)
Corporate events can impact on the value of merging companies and shareholders wealth in both positive and negative ways The study analyzes the impact of mergers and acquisitions as an event on the stock return of the Nepalese financial sector Three models Constant mean return market-adjusted model and CAPM model were used employing the event study methodology to examine abnormal returns because of M A The study has analyzed 20 recent events from five different financial sectors in Nepal The cumulative abnormal return and buy-and-hold abnormal return have been calculated to analyze the impact of M A Qualitative data from interviews with experts in the financial markets merging firms and investment firms were also used The study revealed that M A have an insignificant impact on the stock returns across all financial sectors Similarly the abnormal return during anticipation window adjustment window and total window period of all financial sectors is insignificant which suggests that the M A event don t have a significant impact on the stock